Oil sands: backfill for tailings management - Morton, S; Longo, S (Paste 2023: 25th International Conference on Paste, Thickened and Filtered Tailings, 2023)
Oil sands mining has traditionally been large-scale operations using either truck and shovel or steam-assisted gravity drainage (SAGD) applications. This has meant that exploration and mining of oil sands has focused on large deposits that justify the use of the existing infrastructure and technologies. These large-scale operations also create large areas of land disturbance and have historically generated significant volumes of tailings and process-affected water that need to be managed. There is a new approach that is targeting smaller-scale deposits that do not meet the requirements of either truck and shovel or SAGD. These smaller deposits are often located in pockets, with four to five deposits being co-located in a general footprint, and they are generally closer to the surface than traditional SAGD deposits. The concept is to focus on underground extraction from the surface without the disturbance of truck and shovel and without the infrastructure of SAGD. The concept also allows for the tailings generated after extraction to be used as the feed material for backfilling the underground void. This paper will be one of a series of papers presenting the alternative mining method being developed for small-scale oil sands mining and the backfill strategy to both manage tailings generated from the extraction process and preserve the stability of the underground operations. In addition, the test results from the initial backfill recipe development will be discussed along with the conceptual design for backfill delivery.
Keywords: backfill; paste; alternative mining methods; near-surface voids; oil sands